School social work practice and its challenges in public senior secondary schools In Nigeria (2021)
This paper explored social work practice in public senior secondary schools in Nigeria. Social work is a social institution with social intervention to encourage, enrich and increase the capacities of students to socially function in their communities. This paper used documentary approach in qualitative research methodology. Secondary data were obtained from review of journals, textbooks, and ofcial publications were obtained to outline social work practice, and discuss challenges of school social practice before advocating school social work practice in public senior secondary schools in Nigeria. Challenges of lack of legislation; inadequate social work education, trained personnel, poor funding, remuneration, and professionalism; lack of clarity and awareness about social work and non-certification of practitioners should be remedied by government and other stakeholders to engender safe and ethical practice among social workers and create an enabling environment for students in public senior secondary schools in Nigeria.